Plasma Big Endothelin-1 Levels and Long-Term Outcomes in Patients With Atrial Fibrillation and Acute Coronary Syndrome or Undergoing Percutaneous Coronary Intervention - Lyu, Si-qi; Zhu, Jun; Wang, Juan; Wu, Shuang; Zhang, Han; Shao, Xing-hui; Yang, Yan-min (Frontiers in Cardiovascular Medicine, 2022)
Background This study aimed to evaluate the association between plasma big ET-1 levels and long-term outcomes in patients with atrial fibrillation (AF) and acute coronary syndrome (ACS) or undergoing percutaneous coronary intervention (PCI). Methods A total of 930 patients were enrolled and followed up for a median duration of 2.3 years. According to the optimal cutoff of big ET-1 for predicting all-cause death, these patients were divided into two groups. The primary endpoints were all-cause death and net adverse clinical events (NACE). The secondary endpoints included cardiovascular death, major adverse cardiovascular events (MACE), BARC class ≥ 3 bleeding, and BARC class ≥ 2 bleeding. Cox regressions were performed to evaluate the association between big ET-1 and outcomes. Results Based on the optimal cutoff of 0.54 pmol/l, 309 patients (33.2%) had high big ET-1 levels at baseline. Compared to the low big ET-1 group, patients in the high big ET-1 group tended to have more comorbidities, impaired cardiac function, elevated inflammatory levels, and worse prognosis. Univariable and multivariable Cox regressions indicated that big ET-1 ≥ 0.54 pmol/l was associated with increased incidences of all-cause death [HR (95%CI):1.73 (1.10–2.71), p = 0.018], NACE [HR (95%CI):1.63 (1.23–2.16), p = 0.001], cardiovascular death [HR (95%CI):1.72 (1.01–2.92), p = 0.046], MACE [HR (95%CI):1.60 (1.19–2.16), p = 0.002], BARC class ≥ 3 [HR (95%CI):2.21 (1.16–4.22), p = 0.016], and BARC class ≥ 2 bleeding [HR (95%CI):1.91 (1.36–2.70), p < 0.001]. Subgroup analysis indicated consistent relationships between the big ET-1 ≥ 0.54 pmol/l and the primary endpoints. Conclusion Elevated plasma big ET-1 levels were independently associated with increased risk of all-cause death, NACE, cardiovascular death, MACE, BARC class ≥ 3 bleeding, and BARC class ≥ 2 bleeding in patients with AF and ACS or undergoing PCI.